Mapping the Prevalence and Most Common Types of Potentially Inappropriate Medications (PIMs) in Older Adults with Polypharmacy: A Decade-Long Scoping Review in Nursing Home Settings - I Gede Iswara Pranidhana Putra; Rista Fauziningtyas; Elida Zairina (Universitas Ngudi Waluyo, 2025)
Polypharmacy among older adults significantly influences the prevalence of potentially inappropriate medication (PIMs). Most existing studies have focused on community-dwelling older adults and primary health care settings. However, a comprehensive overview of the use of PIMs among older adults in nursing homes is still lacking. This study aimed to map the scientific evidence regarding the prevalence and most commonly reported PIMs in nursing homes. This scoping review was conducted based on a literature search of four electronic databases on July 29, 2025. We included observational studies published in English that reported the prevalence and types of PIMs in older adults residing in nursing homes. A total of 1,030 records were identified, and 13 studies fulfilled the inclusion criteria. The prevalence of PIM among older adults in nursing homes varied widely, ranging from 27.2% to 96.3%. Benzodiazepines and proton pump inhibitors were the most frequently reported PIMs. All the included studies were conducted in middle- and high-income countries. Future research should address the geographical evidence gap by conducting studies in underrepresented regions, particularly in low- and middle-income countries, to improve the generalizability of the findings.